Metastic Mesothelioma to the Brain: A Potential Differential Diagnosic Challenge - Dalwadi VD; Sheikhi LE; Braun KL; Quist KD; Prayson RA (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Background: Malignant mesothelioma is a rare neoplasm arising from the mesothelial surfaces of the pleural cavity, peritoneal cavity, tunica vaginalis or pericardium that spreads mainly via direct invasion. While distant metastasis is possible, metastasis to the central nervous system (CNS) is rare.                 The Context and Purpose of the Study: We describe a 66-year-old male with a past medical history of mesothelioma, diagnosed approximately 1.5 years prior and treated with resection and chemotherapy, who developed an episode of right facial twitching and was found to have two left cortical frontal masses. After undergoing a frontoparietal craniotomy, the masses were diagnosed as a metastatic mesothelioma. Main Findings: The tumor was characterized by disordered sheets of large, rounded atypical tumor cells with abundant eosinophilic cytoplasm, irregularly shaped nuclei and prominent nucleoli. Prominent mitotic activity and areas of geographic necrosis were also observed. The tumor demonstrated diffuse positive staining with antibody to calretinin, and focal positive staining with antibodies to D2-40 and WT-1. Conclusion: Cerebral metastasis of malignant pleural mesothelioma is a rare, but identifi able cause of neurologic symptoms. Specific immunomarkers including calretinin, WT-1 and D2-40 can help distinguish these tumors from more commonly encountered metastases (carcinomas and melanomas).